Offensive analysis in EUROLEAGUE final four - Edgar Solsona; Jorge Serna; Verónica Muñoz-Arroyave; José Albeiro Echeverri Ramos (Universidade Federal de Santa Catarina, 2020)
The aim of this study is to analyze the influence of the ball screen and 1x1 situations on the shooting effectiveness in the Euroleague Final Four of the 2016-2017 season. A total of 1122 offensive actions were analyzed by means of an ad hoc instrument called SOCCB, where the following findings stand out: a) ball screen is the most used concept followed by one-on-one played outside the three-point line and finally, the one-on-one played close to the zone; b) the limited use of the one-on-one played close to the zone and specialization of the big men in screening and shooting actions rather than team behavior is confirmed; c) almost 60% of basketball procedures (ball screen and one-on-one) studied finish in a pass, which increases the importance of being competent in this aspect of the game and play without the ball; and d) ball screen and one-on-one played close to the zone were actions generating benefits and the one-on-one played outside the three-point line was an action with greater tendency towards shooting.